Multimedia teaching tools in foreign language learning - Cherednichenko, Galina; Shapran, Ludmila (My University, 2014)
The article addresses the impact of multimedia and CALL on language learning within limited curriculum hours, possibility to combine self-study with classroom training and provide systematic feedback, regular progress assessment, dynamic language improvement.
Keywords: multimedia technologies; students’self-study; computerized learning; foreign language learning; мультимедійні технології; самостійна робота студентів; комп'ютеризоване навчання; оволодіння іноземною мовою; кафедра ділової іноземної мови та міжнародної комунікації